The RECARDINA Study protocol: diagnostic utility of ultra-abbreviated echocardiographic protocol for handheld machines used by non-experts to detect rheumatic heart disease. Issue 5 (27th May 2020) - Francis, Joshua Reginald; Fairhurst, Helen; Whalley, Gillian; Kaethner, Alex; Ralph, Anna; Yan, Jennifer; Cush, James; Wade, Vicki; Monteiro, Andre; Remenyi, Bo
Abstract : Introduction: Rheumatic heart disease (RHD) causes significant morbidity and mortality in young people from disadvantaged populations. Early detection through echocardiography screening can facilitate early access to treatment. Large-scale implementation of screening could be feasible with the combination of inexpensive standalone ultrasound transducers and upskilling non-expert practitioners to perform abbreviated echocardiography. Methods and analysis: A prospective cross-sectional study will evaluate an abbreviated echocardiography screening protocol for the detection of latent (asymptomatic) RHD in high-risk populations. The study will evaluate the diagnostic accuracy of health worker conducted single parasternal long axis view with a sweep using handheld devices (SPLASH) (Philips Lumify S4-1 phased array transducer). Each participant will have at least one reference test performed on the same day by an expert echocardiographer. Diagnosis of RHD will be determined by a panel of three experts, using 2012 World Heart Federation criteria. Sensitivity and specificity of the index test will be calculated with 95% CIs, to determine diagnostic accuracy of a screen-and-refer approach to echocardiography screening for RHD. Remote review of SPLASH images obtained by health workers will facilitate evaluation of the sensitivity and specificity of an alternative approach, using external review of health worker obtained SPLASH images to decide onward referral. Ethics and dissemination: Ethics approval was obtained from the Human Research Ethics Committee of the Northern Territory Department of Health and Menzies School of Health Research, for the project to be carried out in Timor-Leste (HREC 2019-3399), and in Australia, following review by the Aboriginal Ethics subcommittee (HREC 2019-334). Ethical and technical approval was granted in Timor-Leste, by the Institute National of Health Research Ethics and Technical Committee (1073-MS-INS/GDE/VII/2019). Study results will be disseminated in the communities involved in the study, and through peer-reviewed publications and conference abstracts. Trial registration number: The Australia New Zealand Clinical Trials Registry (ACTRN12620000122954).